Self-cleaning glass hard film with high definition in rain and preparation method thereof

By depositing a hard film on the glass surface and regulating the micro-nano structure using laser scanning technology, the problem of difficulty in achieving wear resistance, self-cleaning and high definition in rain in the glass surface in the prior art is solved, and higher wear resistance and self-cleaning are achieved, and it is suitable for use in photovoltaic glass, automotive glass and other fields.

CN119774888APending Publication Date: 2025-04-08QINGDAO UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311287520.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve wear resistance, self-cleaning and high definition in rain on the glass surface, especially in harsh environments, the glass surface is easily contaminated by dust, affecting the user experience and power generation efficiency.

Method used

By depositing a hard film on the glass surface and regulating the micro-nano structure array using laser scanning technology, adjusting the film layer thickness and composition, we achieve wear resistance, self-cleaning and high definition in rain.

Benefits of technology

It realizes wear resistance and self-cleaning of the glass surface, ensuring that the field of view does not affect the field of view in rain or harsh environments, and the process is simple, low-cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774888A_ABST
    Figure CN119774888A_ABST
Patent Text Reader

Abstract

The invention discloses a self-cleaning glass hard film with high definition in rain and a preparation method thereof. The preparation method comprises the following steps: (1) depositing a hard film such as a carbide film, a nitride film, an oxide film or a carbon film on glass; and (2) scanning the surface of the glass on which the hard film is deposited by laser to obtain the self-cleaning glass hard film with high definition in rain. The self-cleaning glass hard film with high definition in rain is prepared by adopting a simple process. The prepared glass can be applied to photoelectric screens of mobile phones, PADs, televisions, computers and the like, and also can be applied to occasions needing wear-resistant glass, such as solar glass, locomotive glass and the like. The preparation method disclosed by the invention is low in equipment requirement and low in cost, and has the advantage of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparing self-cleaning, high-definition glass hard film in rain, and prepares corresponding surface structure by adjusting process to achieve wear-resistant, self-cleaning and high-definition effects in rain. It specifically relates to a self-cleaning, high-definition glass hard film in rain and its preparation method. Background Art

[0002] Photoelectric screens such as mobile phone screens, computer screens, TV screens, tablet screens, and solar panels are all prone to dust, which seriously affects the user experience. In particular, dust on the surface of solar panels blocks sunlight and reduces power generation efficiency. Studies have shown that if solar cells are not cleaned for three months, the efficiency may drop by 30%. The entire solar cell market is already a trillion-dollar market, and the losses are very large. More seriously, it may cause hot spot effects. Batteries blocked by dust may be reversely broken down by other batteries in series or even cause fires and other serious consequences. In addition, harsh outdoor environments such as wind, frost, rain, snow, and dust can also have adverse effects, so it is very important that the glass cover is wear-resistant and self-cleaning.

[0003] In addition, the hydrophobic glass jointly developed by Fuyao Glass and Volvo has been used in the rearview mirrors of a very small number of high-end models to improve the clarity of cars driving in the rain. The sol-gel method is used to form a fluoride film layer on the glass surface. It is usually tetrafluorosilane, which is expensive and has certain environmental toxicity and pollution. It is not wear-resistant and has poor durability in dusty environments. The video shown on its official website shows that this hydrophobic glass will still block part of the line of sight during the rolling process of water, and may still block the field of vision in heavy rain. Currently, most rainproof films and rainproof agents on the market also use hydrophobic coating technology. The main problem is that the rolling process of water droplets blocks the line of sight.

[0004] Therefore, the glass prepared by the present invention is hydrophilic glass, which has a strong water spreading ability and forms a continuous water film, so that the field of vision is not affected even by heavy rain. At the same time, the surface material of the glass prepared by the present invention is a hard film, which can be a hard material such as diamond-like carbon film, silicon nitride film, aluminum oxide film, silicon carbide film, so the wear resistance and stability are better.

[0005] The present invention attempts to adopt a technology to solve the above-mentioned self-cleaning, high-definition glass hard film requirements in rain by adjusting technical parameters. Summary of the invention

[0006] The present invention provides a self-cleaning, high-definition glass hard film in rain and a preparation method thereof. The purpose of wear resistance, self-cleaning and high-definition in rain is achieved by changing the film thickness, composition and laser scanning parameters of the hard film to regulate the micro-nano structure array and its microscopic component composition.

[0007] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: The present invention provides a method for preparing a self-cleaning, rain-resistant high-definition glass hard film, comprising the following steps: (1) Deposition of hard films on glass; (2) Laser scanning the glass surface after the hard film is deposited in step (1) to form a micro-nano structure on the glass surface, thereby obtaining a self-cleaning, high-definition glass hard film in rain.

[0008] Furthermore, the glass includes all glass, glass that can be used in the rain, glass that can be used underwater, and glass that can be used inside the body.

[0009] Furthermore, the hard film includes at least one of silicon nitride film, silicon carbide film, carbon film, titanium carbide film, tungsten carbide film, aluminum nitride film, titanium nitride film, and aluminum oxide film; and the deposition thickness of the inorganic thin film is 5nm-50μm.

[0010] Preferably, the deposition thickness of the inorganic thin film is 50nm-1000nm.

[0011] Furthermore, the deposition method includes magnetron sputtering, electron beam evaporation, atomic layer deposition, slit coating, roll-to-roll printing, and dip coating.

[0012] Furthermore, when the deposition method is magnetron sputtering, the typical settings are: a water-cooled SiN target with a sputtering diameter of 60 mm, a sputtering gas of pure Ar, a working gas pressure of 1.6 Pa, an argon gas flow rate of 30 sccm, a sputtering power set to 150w, a substrate heating temperature controlled at 250°C, and a deposition time of 20min.

[0013] In the present invention, different equipment has different process parameters, which can be selected according to actual needs.

[0014] Furthermore, the laser includes at least one of an infrared laser, a visible light laser, an ultraviolet laser, a continuous laser, and a pulsed laser.

[0015] Furthermore, the laser energy density is greater than 50 mJ / cm 2 .

[0016] Preferably, the laser scanning uses a 5W rated power ultraviolet laser. If the laser frequency is 30KHz and the laser spot diameter is 50 microns, the energy density at this time can be estimated to be 8.5 J / cm 2 .

[0017] Furthermore, the laser scanning speed is 0.01 m / s-500 m / s; and the scanning line spacing is ≤10 mm.

[0018] Preferably, the scanning speed of the laser scanning is 0.5 m / s-10 m / s; the scanning power is 1%-100% of the rated power; and the scanning line spacing is 0.1-0.9 mm.

[0019] Furthermore, the self-cleaning, rain-resistant high-definition glass hard film can be used as both an inner surface and an outer surface of glass.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can achieve wear-resistant and self-cleaning performance by using a simple process, which is superior to the existing technology. The existing technology mostly uses nano-titanium dioxide and glue to adhere to the glass surface. The durability of the glue is poor, and the wear resistance of nano-titanium dioxide is not strong. The present invention uses hard films such as silicon carbide, silicon nitride, etc., whose wear resistance far exceeds the existing technology; 2. The present invention can achieve high-definition performance in rain-resistant wear by using a simple process, which is superior to the existing technology. The existing technology uses the sol-gel method to deposit a layer of fluorosilane on the glass surface, which takes a long time, is costly, and is not durable. The present invention uses a hard film layer, so it has good durability; 3. The present invention forms a stable micro-nano structure on the glass surface, achieving a strong water spreading ability on the surface. Therefore, even heavy rain does not affect the field of vision. The prior art uses hydrophobic glass which still blocks part of the field of vision during the rolling process of water, and is likely to block the field of vision in heavy rain; 4. In terms of technology, the deposition method of the present invention uses magnetron sputtering, electron beam evaporation, atomic layer deposition, slit coating, roll-to-roll printing, and dip coating; the requirements for laser scanning are low; the entire preparation method is low-cost and can be completed using industrially stable and mature equipment. Therefore, it can be directly used to produce self-cleaning, rain-resistant high-definition glass hard films, and has the advantage of large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a confocal microscope photo of the surface of the reference glass after sandpaper rubbing in Example 1. It can be seen that there are a lot of scratches on the surface. A 500g weight is placed on a 100*100mm glass, and the glass is dragged back and forth on 600-grit sandpaper for 2 times (single-way 230mm) to complete the sandpaper rubbing experiment. Figure 1a It is a two-dimensional confocal image; Figure 1b This is a three-dimensional confocal image.

[0022] FIG2 is a confocal microscope photo of the surface of the glass treated in Example 1 after the sandpaper friction test. It can be seen that there are almost no scratches on the surface. The sandpaper friction test is illustrated in FIG1. Figure 2a , two-dimensional; Figure 2b , three-dimensional.

[0023] Figure 3It is a comparison diagram of the transmission field of view of the treated glass and the reference glass in Example 1 before sandpaper friction under a mist spray environment.

[0024] Figure 4 It is a comparison diagram of the transmission field of view of the treated glass and the reference glass in Example 1 after being rubbed with sandpaper in a mist water spray environment.

[0025] Figure 5 This is a photograph of the sample surface after the methyl orange solution is evenly sprayed on and rubbed with sandpaper in Example 1.

[0026] Figure 6 The uniform water spray cleaning in Example 1 Figure 5 Surface photograph of the sample.

[0027] Figure 7 This is a confocal microscope photo of the surface of the glass treated in Example 2 after the sandpaper friction test. It can be seen that there are almost no scratches on the surface. The sandpaper friction test is illustrated in Figure 1.

[0028] Figure 8 It is a comparison diagram of the transmission field of view of the treated glass in Example 2 and the reference glass before sandpaper friction in a mist water spray environment.

[0029] Fig. 9 It is a comparison diagram of the transmission field of view of the treated glass and the reference glass in Example 2 after being rubbed with sandpaper in a mist spray environment.

[0030] Fig.10 This is a photograph of the sample surface after the methyl orange solution is evenly sprayed on and rubbed with sandpaper in Example 2.

[0031] Fig.11 The uniform water spray cleaning in Example 2 Fig.10 Surface photograph of the sample.

[0032] Fig.12 This is a confocal microscope photo of the surface of the glass treated in Example 3 after the sandpaper friction test. It can be seen that there are almost no scratches on the surface. The sandpaper friction test is illustrated in Figure 1.

[0033] Fig.13 This is a photograph of the sample surface after the methyl orange solution is evenly sprayed on and rubbed with sandpaper in Example 3.

[0034] Fig.14 The uniform water spray cleaning in Example 3 Fig.13 Surface photograph of the sample.

[0035] Fig.15 This is a confocal microscope photo of the surface of the glass treated in Example 4 after the sandpaper friction test. It can be seen that there are almost no scratches on the surface. The sandpaper friction test is illustrated in Figure 1.

[0036] Fig.16 This is a photograph of the sample surface after the methyl orange solution is evenly sprayed on and rubbed with sandpaper in Example 5.

[0037] Fig.17 The uniform water spray cleaning in Example 5 Fig.16 Surface photograph of the sample.

[0038] Fig.18 This is a confocal microscope photo of the surface of the glass treated in Example 6 after the sandpaper friction test. It can be seen that there are almost no scratches on the surface. The sandpaper friction test is illustrated in Figure 1. DETAILED DESCRIPTION

[0039] The following embodiments are used to better illustrate the present invention, but the present invention is not limited to the following embodiments.

[0040] Example 1: Laser scanning of carbon-coated films to prepare self-cleaning, rain-resistant high-definition glass hard films

[0041] The specific steps of the preparation method of the high-definition glass hard film in rain and underwater based on carbon film are as follows: (1) Carbon film was deposited on soda-lime glass using a magnetron sputtering coating system: RF sputtering of a water-cooled graphite target (99.99%) with a diameter of 60 mm; the sputtering gas was pure Ar (99.9995%), the working pressure was 1.6 Pa, the argon flow rate was set to 30 sccm, the sputtering power was controlled at 150 W, the substrate heating temperature was 250 °C, and the carbon coating time was 20 min; (2) Laser scanning: The surface of the soda-lime glass after the carbon film deposition in step (1) is scanned by a 5W ultraviolet laser with a frequency of 30KHz, a pulse width of 8 microseconds, a scanning speed of 4m / s, and a scanning line spacing of 0.1 and 0.2mm; a high-definition glass in the rain is obtained, and the glass has a certain wear resistance and still maintains high definition in the rain after sandpaper rubbing. The reference glass and the treated glass are respectively pressed under a 500g weight and dragged back and forth on 600-mesh sandpaper for 2 times (the width of the sandpaper is 230mm per one-way). The sample after sandpaper rubbing is subjected to the subsequent self-cleaning and high-definition experiments in the rain. Figures 1 and 2 are confocal microscope images of the surface after sandpaper rubbing. Figure 1a 2D, Figure 1b 3D, showing the surface wear scar of the reference glass after rubbing on sandpaper; Figure 2a 2D, Figure 2b The three-dimensional image shows the surface scratches of the treated glass after being rubbed by sandpaper. It can be seen that there are almost no scratches on the surface of the treated glass, and it has strong wear resistance. Figure 3 It shows that before sandpaper rubbing, water was sprayed to simulate a rainy scene. The treated glass had a clear transmission field of view; while the reference glass had a blurred field of view with many water droplets. Figure 4The image shows that after sandpaper rubbing and water spraying to simulate a rainy scene, the treated glass still has a clear view, while the reference glass has a blurred view with many water droplets. Figure 3 , 4 Even the treated glass has treated areas and untreated areas, and water droplets will remain in the untreated areas. Figure 5 This is a photo of the sample surface after evenly spraying methyl orange solution on the sandpaper rubbed surface. Figure 6 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the surface of the treated area, which has a strong self-cleaning ability. However, methyl orange still remains in the untreated edge area, which has no self-cleaning ability. Figure 6 The edge parts with residual water droplets are all untreated reference glass areas.

[0042] Example 2: Laser scanning of silicon nitride film to prepare self-cleaning, rain-resistant high-definition glass hard film The specific steps of the preparation method of the self-cleaning, high-definition glass hard film in rain based on silicon nitride film are as follows: Silicon nitride film was deposited on glass by magnetron sputtering coating system, and a water-cooled silicon nitride target (99.99%) with a diameter of 60 mm was sputtered by RF. The sputtering gas was pure Ar (99.9995%), the working gas pressure was 1.6 Pa, the argon flow rate was set to 30 sccm, the sputtering power was controlled at 150 W, the substrate heating temperature was set at 250 °C, and the deposition time was 20 min.

[0043] Laser scanning the glass surface after the silicon nitride film is deposited in step (1) to form a micro-nano structure on the glass surface; using a 5W ultraviolet laser with a rated power of 30KHz, a pulse width of 8 microseconds, a scanning speed of 4m / s, and a scanning line spacing of 0.1mm and 0.2mm; a self-cleaning and high-definition glass hard film in the rain is obtained. The reference glass and the treated glass are respectively pressed under a 500g weight and dragged back and forth on 600-grit sandpaper (sandpaper width is 230mm) for 2 times. The samples after sandpaper rubbing are subjected to the subsequent self-cleaning and high-definition in the rain experiments. Figure 7 This is a confocal microscope photo of the treated glass after being rubbed with sandpaper. The picture shows that there are no wear marks on the surface. Compared with the dense and deeper wear marks on the reference glass in Figure 1, it demonstrates excellent wear resistance. Figure 8 It shows that before sandpaper rubbing, water was sprayed to simulate a rainy scene. The treated glass had a clear transmission field of view; while the reference glass had a blurred field of view with many water droplets. Fig. 9 The image shows that after sandpaper rubbing and water spraying to simulate a rainy scene, the treated glass still has a clear view, while the reference glass has a blurred view with many water droplets. Figure 8 , 9 Even the treated glass has treated areas and untreated areas, and water droplets will remain in the untreated areas. Fig.10 This is a photo of the sample surface after evenly spraying methyl orange solution on the sandpaper rubbed surface. Fig.11 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the surface of the treated area, which has a strong self-cleaning ability. However, methyl orange still remains in the untreated edge area, which has no self-cleaning ability. Fig.11 The edge parts with residual water droplets are all untreated reference glass areas.

[0044] Example 3: Preparation of self-cleaning glass hard film by laser scanning of coated silicon carbide film: The specific steps of the preparation method of self-cleaning glass hard film based on silicon carbide film are as follows: (1) Magnetron sputtering deposition of silicon carbide film on glass: sputtering water-cooled silicon carbide target (99.995%) with a diameter of 60 mm, sputtering gas pure Ar (99.9995%), working pressure 1.6 Pa; argon gas flow rate 30 sccm, RF sputtering power 150 W, substrate heating temperature set to 250 °C, deposition time 20 min; (2) Laser scanning The glass surface after the silicon carbide film is deposited in step (1) is laser scanned with a UV laser with a rated power of 5W: frequency 30KHz, pulse width 8 microseconds, scanning speed 4m / s, scanning line spacing 0.5mm; a self-cleaning glass hard film is obtained. The reference glass and the treated glass are respectively pressed under a 500g weight and dragged back and forth on 600-grit sandpaper (sandpaper width 230mm) for 2 times. The samples after sandpaper rubbing are subjected to the following self-cleaning experiment. Fig.12 This is a confocal microscope photo of the treated glass after being rubbed with sandpaper. The picture shows that there are no wear marks on the surface. Compared with the dense and deeper wear marks on the reference glass in Figure 1, it demonstrates excellent wear resistance. Fig.13 This is a photo of the sample surface after evenly spraying methyl orange solution on the sandpaper rubbed surface. Fig.14 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the surface of the treated area, which has a strong self-cleaning ability. However, methyl orange still remains in the untreated edge area, which has no self-cleaning ability. Fig.14 The edge parts with residual water droplets are all untreated reference glass areas.

[0045] Example 4: Laser scanning titanium nitride film to prepare glass hard film: The specific steps of the method for preparing glass hard film based on titanium nitride film are as follows: (1) Titanium nitride film was deposited on glass using a magnetron sputtering coating system, using a water-cooled titanium nitride target (99.99%) with a diameter of 60 mm for RF sputtering. The sputtering gas was pure Ar (99.9995%), the working pressure was 1.6 Pa, the argon flow rate was set to 30 sccm, the sputtering power was controlled at 150 W, the substrate heating temperature was set at 250 °C, and the deposition time was 20 min. (2) Laser scanning: The glass surface after the titanium nitride film is deposited in step (1) is scanned by a 5W ultraviolet laser with a frequency of 30KHz, a pulse width of 8 microseconds, a scanning speed of 4m / s, and a scanning line spacing of 0.1-0.9mm to obtain a glass hard film. The reference glass and the treated glass are respectively pressed under a 500g weight and dragged back and forth on a 600-grit sandpaper (the sandpaper width is 230mm) for 2 times. Fig.15 This is a confocal microscope photo of the treated glass after being rubbed with sandpaper. The picture shows that there are no wear marks on the surface. Compared with the dense and deeper wear marks on the reference glass in Figure 1, it demonstrates excellent wear resistance.

[0046] Example 5: Preparation of self-cleaning glass by laser scanning of titanium carbide film The specific steps of the preparation method of self-cleaning glass based on titanium carbide film are as follows: Titanium carbide film was deposited on glass by magnetron sputtering coating system. The glass used was soda-lime glass or borosilicate glass. A water-cooled titanium carbide target (99.99%) with a diameter of 60 mm was RF sputtered. The sputtering gas was pure Ar (99.9995%). The working gas pressure was 1.6 Pa. The argon gas flow rate was set to 30 sccm. The sputtering power was controlled at 150 W. The substrate heating temperature was set at 250 °C. The titanium carbide coating time was 20 min.

[0047] Laser scanning the glass surface after titanium carbide film deposition in step (1) uses a 5W ultraviolet laser with a rated power of 30KHz, a pulse width of 8 microseconds, a scanning speed of 4m / s, and a scanning line spacing of 0.1-0.9mm to obtain a self-cleaning glass Fig.16 This is a photo of the sample surface after evenly spraying methyl orange solution on the sandpaper rubbed surface. Fig.17 This is a photo of the surface after uniform water spray cleaning. It can be seen that there is no methyl orange residue on the surface of the treated area, which has a strong self-cleaning ability. However, methyl orange still remains in the untreated edge area, which has no self-cleaning ability. Fig.17 The edge parts with residual water droplets are all untreated reference glass areas.

[0048] Example 6: Preparation of glass hard film by laser scanning of tungsten carbide film The specific steps are as follows: (1) A tungsten carbide film was deposited on glass using a magnetron sputtering coating system. A water-cooled tungsten carbide target (99.99%) with a diameter of 60 mm was sputtered by radio frequency. The sputtering gas was pure Ar (99.9995%), the working gas pressure was 1.6 Pa, the argon gas flow rate was set to 30 sccm, the sputtering power was controlled at 150 W, the substrate heating temperature was set at 250 °C, and the tungsten carbide coating time was 20 min.

[0049] (2) Laser scanning: After the tungsten carbide film is deposited in step (1), the surface of the soda-lime glass or borosilicate glass is scanned by a 5W ultraviolet laser with a frequency of 30KHz, a pulse width of 8 microseconds, a scanning speed of 4m / s, and a scanning line spacing of 0.1mm-0.9mm to obtain a glass hard film. The reference glass and the treated glass are respectively pressed under a 500g weight and dragged back and forth on a 600-grit sandpaper (the sandpaper width is 230mm) for 2 times. Fig.18 This is a confocal microscope photo of the treated glass after being rubbed with sandpaper. The picture shows that there are only two shallow wear marks on the surface, which is compared with the dense and deeper wear marks on the reference glass in Figure 1, demonstrating its excellent wear resistance.

[0050] As described in the above embodiments, the surface structure is formed on the glass surface by adjusting the process parameters using equipment that can be mass-produced, thus having the advantage of being mass-produced. The glass obtained by the above preparation method of the present invention has the characteristics of wear resistance, self-cleaning, high definition in rain and underwater, and can be used to produce self-cleaning, rain and underwater glass, such as photovoltaic glass cover, motor vehicle rearview mirror, front windshield, train and airplane glass, medical endoscope, and other rain and underwater glass. It can also be used to produce various types of optoelectronic screens that require wear resistance and self-cleaning properties, such as mobile phones, tablets, computers, and TV screens.

[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for preparing a self-cleaning, rain-resistant high-definition glass hard film, characterized in that: The following steps are involved: (1) Deposition of hard films on glass; (2) Laser scanning the glass surface after the hard film is deposited in step (1) to obtain a self-cleaning, high-definition glass hard film in rain.

2. The method for preparing a self-cleaning, rain-resistant high-definition glass hard film according to claim 1, characterized in that: The glass includes all glass, glass that can be used in rain, and glass that can be used underwater.

3. The method for preparing a self-cleaning, rain-resistant high-definition glass hard film according to claim 1, characterized in that: The inorganic thin film includes at least one of silicon nitride film, silicon carbide film, carbon film, titanium carbide film, tungsten carbide film, aluminum nitride film, titanium nitride film and aluminum oxide film; the deposition thickness of the inorganic thin film is 5nm-50μm.

4. The method for preparing a self-cleaning, rain-resistant high-definition glass hard film according to claim 1, characterized in that: The deposition methods include magnetron sputtering, electron beam evaporation, atomic layer deposition, slit coating, roll-to-roll printing, and dip coating.

5. According to the method for preparing the self-cleaning, high-definition glass hard film in the rain as described in claim 1, the laser includes an infrared laser, a visible light laser, an ultraviolet laser; at least one of a continuous laser and a pulsed laser.

6. The method for preparing a self-cleaning, rain-resistant high-definition glass hard film according to claim 1, characterized in that: The laser energy density is greater than 50 mJ / cm 2 .

7. The glass prepared according to claim 1 can be used for photovoltaic screens, solar glass, motorcycle glass, and glass that can be used in rain, underwater, and in body fluids.

8. The self-cleaning, high-definition glass hard film in rain prepared by the preparation method according to any one of claims 1 to 7 and its application, characterized in that: The high-definition glass for use in rain or underwater can be used as the inner surface of glass, and can also be used as the outer surface of glass.